METHODOLOGY FOR USING FOLK AND ACTIVITY GAMES IN PHYSICAL EDUCATION LESSONS (CONFERENCE ON THE ROLE AND IMPORTANCE OF SCIENCE IN THE MODERN WORLD, 2024)
It is known that Uzbek folk games include games aimed at developing various physical qualities. Therefore, it is considered necessary to distinguish them according to their directions. Therefore, their classification (classification) takes the necessary place. In this regard, we believe that it would be appropriate to use Uzbek folk games in the middle of the lesson